Tourism development for community capacity building and community development - Aref, Fariborz; Redzuan, Ma'rof (Tourism Educators Association of Malaysia, 2008)
Community capacity building is widely acknowledged as an important community development strategy. Its strength lies in its ability to empower community members as citizens to self-manage their lives and environment through facilitating leadership and participation in the building and enactment of shared community vision. In this way tourism has become increasingly important as a contributor for community capacity building in local communities. Many communities also recognize that tourism can stimulate change in social, cultural and environmental dimensions as well. The purpose of this paper is to explore the concept of community capacity building and community development with respect to tourism development.